2017
DOI: 10.1051/kmae/2017041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of flow events and nutrient addition on stream periphyton and macroinvertebrates: an experimental study using flumes

Abstract: -We used flume experiments to study the effects of a temporary increase in stream flow on macroinvertebrates, leaf litter breakdown and soft-bodied benthic algae; both as a single stressor and eventually in combination with an increase in nutrient supply. In order to understand how well the flumes reflected the nearby stream ecosystem, we compared species composition of macroinvertebrates and benthic algae between the flumes and the nearby stream from which the flumes were supplied with water. As single stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 59 publications
2
10
0
Order By: Relevance
“…However, exploitation of freshwater resources such as industrial abstractions, hydropower generation, and drinking water supply has significantly altered natural flow dynamics across the globe (Poff et al, ); 37% of European rivers are affected by flow regulation (http://www.ecologic.eu/11663) and, in Norway, where hydropower provides >95% of the total electricity generated, more than two thirds of river basins are affected by hydromorphological alteration (http://www.nve.no). Understanding the effects of flow alteration on aquatic ecology is crucial for the sustainable management of regulated river systems, but linking indicators of hydrological change to ecology is not straightforward because (a) properly replicated and controlled experiments are rarely possible in practice in fluvial ecosystems (Richter et al, ), (b) species assemblages in experimental flumes often differ from the assemblages in adjacent watercourses, raising questions on the relevance of flume experiments (Bækkelie, Schneider, Hagman, & Petrin, ), and (c) field data may reflect the effects of correlated variables rather than the effects of the variables of interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, exploitation of freshwater resources such as industrial abstractions, hydropower generation, and drinking water supply has significantly altered natural flow dynamics across the globe (Poff et al, ); 37% of European rivers are affected by flow regulation (http://www.ecologic.eu/11663) and, in Norway, where hydropower provides >95% of the total electricity generated, more than two thirds of river basins are affected by hydromorphological alteration (http://www.nve.no). Understanding the effects of flow alteration on aquatic ecology is crucial for the sustainable management of regulated river systems, but linking indicators of hydrological change to ecology is not straightforward because (a) properly replicated and controlled experiments are rarely possible in practice in fluvial ecosystems (Richter et al, ), (b) species assemblages in experimental flumes often differ from the assemblages in adjacent watercourses, raising questions on the relevance of flume experiments (Bækkelie, Schneider, Hagman, & Petrin, ), and (c) field data may reflect the effects of correlated variables rather than the effects of the variables of interest.…”
Section: Introductionmentioning
confidence: 99%
“…alteration (www.nve.no). Understanding the effects of flow alteration on aquatic ecology is crucial for the sustainable management of regulated river systems, but linking indicators of hydrological change to ecology is not straightforward because (a) properly replicated and controlled experiments are rarely possible in practice in fluvial ecosystems , (b) species assemblages in experimental flumes often differ from the assemblages in adjacent watercourses, raising questions on the relevance of flume experiments (Baekkelie, Schneider, Hagman, & Petrin, 2017), and (c) field data may reflect the effects of correlated variables rather than the effects of the variables of interest.…”
mentioning
confidence: 99%
“…The literature shows contrasting effects of water discharge on biofilms. Some studies reported no response for algal biomass [54][55][56] as well as for metabolism [14,54], whereas others showed that algal biomass decreased both above and below optimum velocities, a fact that would be explained by shear stress at high velocities, by nutrient limitation at low ones. This is the type of response reported by Biggs and Stokseth [57] where the algal biomass peaked at a velocity of 30 cm s -1 .…”
Section: Discussionmentioning
confidence: 99%
“…However, for flow management and restoration to be fully successful, it is important to consider the effects of other influencing factors at various spatial scales (King et al, 2016;Verdonschot et al, 2016). Such a task is complicated by interactive effects that modify the impact of confounding factors (Folt et al, 1999), such as habitat complexity dampening the strength of temperature effects (Scrine et al, 2017) or a combined effect of flow velocity and increased nutrient concentrations being smaller than the individual impact (Baekkelie et al, 2017).…”
Section: Limitationsmentioning
confidence: 99%